Antibacterial Effect and Potency of Jamaican Cherry Leaves (Muntingia calabura L.) as Feed Additive for Antibiotic Growth Promoter Alternative in Animals - Anak Agung Gede Fandhiananta Widyanjaya; Anak Agung Gede Jayawardhita (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2021)
Antimicrobial resistance is one of the greatest health challenges in the world. The unwise use of Antibiotic Growth Promoter (AGP) in livestock is one of the factors that triggers the increase in the incidence of antimicrobial resistance. In an effort to anticipate the negative impact of using antibiotics, alternative materials are needed to replace AGP. From those various problems, this paper aims to provide information on the use of phytogenic feed additives as natural antibacterials that have the potency as an alternative AGP. Based on the results of various studies, Jamaican cherry leaf extract has the ability to inhibit the growth of various bacterial species in vitro. Various phytochemical test results showed that Jamaican cherry leaves contain several types of phenolics, flavonoids, tannins, and saponins that have antibacterial effect.  The addition of Jamaican cherry leaves to feed was able to increase the value of digestibility, carcass weight, egg production, and protein content of meat. Therefore, Jamaican cherry leaf (Muntingia carabula L.) has the potency to be used as feed additive to replace AGP.